Impact of the age at menarche on body composition in adulthood: results from two birth cohort studies - Susana Bubach; Ana Maria Baptista Menezes; Fernando Celso Barros; Fernando César Wehrmeister; Helen Gonçalves; Maria Cecília Formoso Assunção; Bernardo Lessa Horta (BMC, 2016)
Abstract Background Evidence suggests that early menarche is positively associated with adiposity in adulthood. However, it is important to assess whether this association is due to early menarche or to the association of adiposity in late childhood with age at menarche. We evaluated the association between age at menarche and body composition in adolescence and adulthood, among subjects who have been prospectively followed in two Brazilian birth cohort studies. Methods In 1982 and 1993, the hospitals births in Pelotas were identified, and these subjects have been followed for several times. Information on age at menarche was obtained from the women (1982 cohort) and their mothers (1993 cohort). At 30 and 18 years, the following body composition measures were evaluated: body mass index, waist circumference, fat-free mass index and fat mass index measured by dual-energy x-ray absorptiometry, and thickness of the abdominal visceral fat layer measured by ultrasound. The analyses were adjusted for: birth weight, maternal pregestational weight, gestational age, family income, household score index, maternal schooling, weight-for-height z-score at 4 years (1982), and body mass index at 11 years (1993). Results At 30 and 18 years, 2045 and 2092 women were evaluated, respectively. The prevalence of early menarche (≤11 years of age) was 24.7 % in the 1982 and 27.6 % in the 1993 cohort. In the 1982 cohort, early menarche was positively associated with all body composition variables compared to those with late menarche (≥14 years of age) even after adjusting for confounders (fat mass index: 2.33 kg/m2, 95 % Confidence interval: 1.64; 3.02). However, in the 1993 cohort, after adjusting for body mass index at 11 years, the regression coefficient for the association with fat mass index decreased from 2.2 kg/m2 (95 % Confidence interval: 1.7; 2.6) to 0.26 (95 % Confidence interval: −0.08; 0.60). Conclusions The association between age at menarche and body composition in adulthood is strongly explained by pre-pubertal adiposity.